Editorial [Hot Topic: Nano-Combinatorial Chemistry and Associated Technologies (Guest Editor: Bing Yan)] - Yan, Bing (Combinatorial Chemistry & High Throughput Screening, 2011)
Nanotechnology refers to the creation of functional materials, devices, and systems through the control of matter at the nanometer scale, and the exploitation of novel phenomena and properties at that scale. Advances in nanotechnology will have tremendous impacts on every aspect of our society. The discovery and optimization of novel functional nanomaterials with unique properties require a time-consuming research efforts. Parallel reactions and screenings are deemed to be more efficient than conventional linear operations. Combinatorial chemistry has already revolutionized drug discovery and the discovery of materials, catalysts, and polymers. It has recently also made a significant impact on nanotechnology. In this issue of Combinatorial Chemistry and High Throughput Screening, we provide an overview of research progresses in the powerful combination between combinatorial chemistry and nanotechnology. The discovery of functional nanomaterials has been dramatically improved by introducing combinatorial methods. Such developments are exemplified by catalyst and nanosized catalyst discoveries described by Zhou, Gao and their coworkers. Glycobiology is an important frontier of research, glycosylated nanoparticles have unique biological activities and amenable for high throughput chemistry research. Dong has provided an update in this area. Application of nanoparticles in high throughput separation and analysis, especially in solidphase extraction is reviewed by Liang and Zhang. As in early days of combinatorial chemistry, analytical technology is key to the success of nano-combinatorial chemistry. Liu and Yan provided a timely review on analytical techniques for nanoparticle modifications and a comparison with techniques in solid-phase synthesis. Accompanied these developments, the screening of nanomaterials were facilitated by the development of many parallel screening technologies. These developments are highlighted by articles from Rajan and Milani and coworkers. Computation and modeling are crucial technologies for nanocombinatorial chemistry and associated biological investigations. Tropsa pioneered in this research effort and provided an excellent review on the progresses in this area. With rapid development of nanotechnology, there is rarely an area without being influenced by this technology. We expect that nano-combinatorial chemistry will play an even more important role in future.